2014
DOI: 10.3748/wjg.v20.i47.18038
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic esophagitis in patients with esophageal atresia and chronic dysphagia

Abstract: Esophageal atresia (EA) is defined as a discontinuity of the lumen of the esophagus repaired soon after birth. Dysphagia is a common symptom in these patients, usually related to stricture, dysmotility or peptic esophagitis. We present 4 cases of patients with EA who complained of dysphagia and the diagnosis of Eosinophilic esophagitis (EoE) was made, ages ranging from 9 to 16 years. Although our patients were on acid suppression years after their EA repair, they presented with acute worsening of dysphagia. Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 34 publications
3
25
1
7
Order By: Relevance
“…In EA, strictures are dilated routinely; however, in EoE, it has been demonstrated that topical corticosteroids may reverse the fibrotic subepithelial process. Esophageal strictures have been reported in patients with EA and EoE at a 18,21,24 In the study carried out by Dhaliwal et al, patients with EoE significantly required a fundoplication more frequently than those without EoE, whereas no differences were observed in terms of gastrostomy requirements. 18 A retrospective study by Chan et al assessed the outcomes of treatment for EoE in children with EA.…”
Section: Esophageal Atresia and Eosinophilic Esophagitismentioning
confidence: 86%
See 3 more Smart Citations
“…In EA, strictures are dilated routinely; however, in EoE, it has been demonstrated that topical corticosteroids may reverse the fibrotic subepithelial process. Esophageal strictures have been reported in patients with EA and EoE at a 18,21,24 In the study carried out by Dhaliwal et al, patients with EoE significantly required a fundoplication more frequently than those without EoE, whereas no differences were observed in terms of gastrostomy requirements. 18 A retrospective study by Chan et al assessed the outcomes of treatment for EoE in children with EA.…”
Section: Esophageal Atresia and Eosinophilic Esophagitismentioning
confidence: 86%
“…Gorter et al have proposed that mutations in the FOX gene not only cause congenital malformations in the esophagus and lung but may also predispose to EoE, so patients with EA may be at a high risk for EoE. 3,6,21 The above mentioned observations suggest that EoE should be taken into consideration when making a differential diagnosis in patients with EA who have dysphagia and refractory gastroesophageal reflux symptoms before considering anti-reflux surgery. 3,21 The age of onset of EoE and EA ranges from 18 months to 12.5 years, and this entity is more common among men, except for the study by Dhaliwal et al, where it was predominant among women (1.6:1).…”
Section: Esophageal Atresia and Eosinophilic Esophagitismentioning
confidence: 99%
See 2 more Smart Citations
“…Gorter y col. postulan que mutaciones en el gen FOX no solo llevan a malformaciones congénitas de esófago y pulmón, sino que podrían predisponer a EEo, por lo cual pacientes con AE podrían tener alto riesgo de EEo. 3,6,21 Las observaciones anteriores sugieren que la EEo debe considerarse como diagnóstico diferencial en pacientes con AE que tienen disfagia y síntomas de reflujo gastroesofágico refractarios antes de considerar la cirugía antirreflujo. 3,21 La disfagia persistente en pacientes con AE debe evaluarse con esofagograma y VEDA + múltiples biopsias.…”
Section: Atresia De Esófago Y Esofagitis Eosinofílicaunclassified